The Incremental Information in SFAS No. 33 Income Disclosures over Historical Cost Income and Its Cash and Accrual Components - Lobo, Gerald J.; Song, In-Man (The Accounting Review, 1989)
[This study investigates the incremental information in alternative measures of constant dollar and current cost operating income reported under SFAS No. 33 over historical cost income and its cash and accural components. To do so, it examines contemporaneous associations between unexpected returns at the time of release of the annual report or 10-K report and variables measuring the unexpected components of these alternative income measures. The research design exploits the difference in timing of the release of historical cost income and of SFAS No. 33 income. The empirical analysis indicates that current cost and constant dollar operating income measures have incremental information over historical cost income and its cash and accural components. The results also indicate that there is incremental information in cash flow over that conveyed by alternative measures of constant dollar and current cost operating income. However, incremental information in SFAS No. 33 measures and of cash flow is observed only for a subset of the industries examined.]